Enhancing linear switched reluctance motor performance through stator winding overhang leakage flux integration - Nisha Prasad; Mahipal Bukya (Discover Applied Sciences)
Abstract High-speed rail transit systems are smoothly finding their way into the mainstream of public transport systems worldwide. The linear motors form an integral part of these transit systems. Thus, the search for an efficient and cost-effective linear motor is inevitable. Linear Switched Reluctance Motors (LSRMs) are gaining the attention of many researchers due to their inherent advantages over other popular linear motors. This paper focuses on enhancing the propulsion force of the motor by proposing some design adjustments to include the leakage flux from the stator winding overhang part. This is done by suggesting some structural changes in the translator of the motor. The impact of modifying the translator on propulsion and ripple reduction is studied using the FEM simulations. An LSRM structure with a split-teeth stator is used for this study. To comparatively analyse the proposed design the same LSRM is studied and analysed with three structural modifications in the translator. The detailed analysis results show the increase in propulsion force of the proposed LSRM by incorporating the leakage flux from the stator winding overhang with reduced force ripples, material weight and cost.